Reversal of perturbed DNA damage response and HIV latency by a histone methyltransferase inhibitor in virally suppressed individuals living with HIV - Chavan, Pragati; Koar, Sathi; Bingewar, Rohini; Sonawane, Anuja; Sawant, Jyoti; Shidhaye, Pallavi; Rao, Amrita; Bagul, Rajani; Ghule, Ujjwala; Kumbhar, Sunita; Ghate, Manisha; Shete, Ashwini (Frontiers in Aging, 2025)
BackgroundOxidative stress contributes to DNA damage, further leading to cellular senescence. HIV infection increases oxidative stress and interferes in DNA damage response. Hence, a study was conducted to assess the extent of DNA damage by evaluating global methylation, 8-hydroxy-2′-deoxyguanosine (8-OHdG), and prelamin A levels in people living with HIV (PLHIV), representing alterations at the genetic, epigenetic, and structural levels. We also investigated the effect of methylation modulators on these markers and HIV latency reversal.MethodsMiddle-aged virally suppressed PLHIV on long-term antiretroviral therapy (ART) and non-infected controls were enrolled for the study. The levels of 5-methylcytosine in blood and plasma 8-OHdG were assessed using commercially available colorimetric and ELISA kits, respectively. Reactive oxygen species (ROS) and prelamin A expression in T cells were assessed by flow cytometry. The levels of DNA damage markers were analyzed for their correlation with immunosenescent and inflammatory markers. Samples were treated with RG108 and chaetocin to assess their effect on these markers and HIV reactivation. HIV reactivation was assessed by the expression of intracellular P24 by flow cytometry and gag copies by real-time PCR.ResultsPLHIV had significantly lower global DNA methylation levels and higher 8-OHdG and prelamin A levels than their age-matched HIV-uninfected controls. The ROS levels did not differ significantly among them. Global methylation and prelamin A levels correlated with immunosenescent T cells. The 8-OHdG levels correlated positively with angiotensin-II levels and negatively with proinflammatory cytokines. Treatment with chaetocin increased the global methylation levels and diminished prelamin A accumulation in CD4+ T cells in PLHIV. P24-expressing CD4+T cells increased significantly after chaetocin treatment, indicating HIV latency reversal.ConclusionPLHIV on ART had higher DNA damage-related markers despite having comparable ROS levels than their age-matched controls. The immunotherapeutic potential of chaetocin for reversing premature aging as well as HIV latency needs to be explored further.